Collective Action in Digital Activism: How Hashtags Mobilize Social Movements - Maulana, Rizky; Nindia, Nurul Fitri; Afifah (Mahogany Journal De Social, 2025)
In the digital era, social movements increasingly take place on online platforms where hashtags function as tools for mobilization, identity, and solidarity. This study explores how hashtags encourage collective action among Indonesian netizens by examining participation patterns, perceived impacts, and barriers to digital activism. Using a mixed-method design, data were gathered from a survey of 400 respondents across Indonesia and supported by digital content observation and case studies. Results show that youth aged 21–30 and students are the most active participants, mainly using Twitter and Instagram. Most engage weekly, and sharing or reposting hashtags is the dominant form of participation, while offline involvement remains limited. Hashtags are considered highly effective in promoting awareness and unity but less influential in shaping policy outcomes. Challenges include short-lived attention, misinformation, and online harassment. The findings highlight that hashtag activism in Indonesia strengthens collective consciousness yet struggles to achieve structural change, emphasizing the need to integrate digital advocacy with community-based and offline initiatives for sustainable impact.